PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENUMBUHKEMBANGKAN SIKAP PERCAYA DIRI PESERTA DIDIK PADA MUATAN PELAJARAN IPAKELAS V SDN MANGKURA IV KECAMATAN UJUNG PANDANG KOTA MAKASSAR - Rezki Yanti Ismail (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2023)
The problem in this study is the lack of students' self-confidence in learning science in class V. The problem in this study is how to apply the Problem Based Learning learning model to develop students' self-confidence in Science Class V SDN Mangkura IV, Ujung Pandang District, Makassar City . The purpose of this study was to describe the application of the problem-based learning model in developing students' self-confidence in science content in class V SDN Mangkura IV, Ujung Pandang District, Makassar City. This research approach is qualitative. This type of research is classroom action research (CAR) conducted in two cycles. The focus of this research is to focus on the learning process and increasing students' self-confidence. The subjects in this study were fifth grade students at SDN Mangkura IV, Ujung Pandang District, Makassar City in 2023, with a total of 25 students consisting of 13 boys and 12 girls, as well as a teacher. Data collection techniques used are observation and documentation. Data analysis techniques show that there is an increase in student learning outcomes in each cycle. The results of the first cycle are in the sufficient category and there is an increase in the second cycle in the good category. So it can be concluded that the classroom action research shows that the science learning process and the confidence of students in class V SDN Mangkura IV, Ujung Pandang sub-district, Makassar City by applying the Problem Based Learning learning model can experience an increase.